DETERMINATION OF PHARMACEUTICAL INDUSTRIAL DISTRIBUTION CENTER LOCATION USING CENTER OF GRAVITY METHOD: CASE STUDY AT PT JKT - Bayu Irwanto; Sawarni Hasibuan (Universitas Mercu Buana, 2018)
Distribution center has an important role in an industry's supply chain management to facilitate logistics management requirements so that the product distribution process becomes smooth and fast. The purpose of this study is to determine the best location that can be used in determining the location of the distribution cente in pharmaceutical industry. This research uses the center of gravity method to calculate optimal location that will be considered. From the results of this study, the calculation using the Center of Gravity method found that the location of the selected distribution center was at the coordinates (-6.257108; 106.7315), the settlement area of the village of Jurangmangu Timur. The available area according to warehousing rules does not allow the construction of the distribution center in residential area of Jurangmangu Bintaro village, empty area is available around 4 KM west of T8 Pakulonan Alam Tangerang Selatan, this area provides warehousing by offering a combined trading center, office and integrated food and beverage plaza with shelter have advantages as distribution center. The new proposed distribution center location is located 14 KM south and 13 KM from the north of the available warehouse, the new suggested location is closer to and located between current distribution locations.